Embryology in Helosis cayennensis (Balanophoraceae): Structure of Female Flowers, Fruit, Endosperm and Embryo - González, Ana María (2019)
Helosis cayennensis (Balanophoraceae s.str.) is a holoparasite characterised by aberrant vegetative bodies and tiny, reduced unisexual flowers. Here, we analysed the development of female flowers to elucidate their morpho-anatomy and the historical controversy on embryo sac formation. We also studied the developmental origin of inflorescences and the ontogeny of fruits, embryo and endosperm and discussed in a phylogenetic framework. Inflorescences were analysed by optical, fluorescence and scanning electron microscopy. Inflorescences of H. cayennensis arise endogenously. Female flowers lack perianth organs, thus only consist of the ovary, two styles and stigmata. Ovules are undifferentiated; two megaspore mother cells develop inside a nucellar complex. The female gametophyte, named Helosis-type, is a bisporic four-celled embryo sac, provided with a typical egg apparatus and a uni-nucleated central cell. Fertilization was not observed, yet a few-celled embryo and cellular endosperm developed. In sum, results confirm that, among Santalales holoparasites, Helosis is intermediate in the reduction series of its floral organs. Although perianth absence best supports the Balanophoraceae s.str. clade, our literature survey on female flower developmental data across Balanophoraceae s.l. highlights the many gaps that need to be filled to really understand these features in the light of new phylogenetic relationships